CD4+ T cells regulate glucose homeostasis independent of adipose tissue dysfunction in mice. Issue 6 (4th May 2021) - Brinker, Georg; Froeba, Janine; Arndt, Lilli; Braune, Julia; Hobusch, Constance; Lindhorst, Andreas; Bechmann, Ingo; Gericke, Martin
Abstract: Obesity is frequently associated with a chronic low‐grade inflammation in the adipose tissue (AT) and impaired glucose homeostasis. Adipose tissue macrophages (ATMs) have been shown to accumulate in the inflamed AT either by means of recruitment from the blood or local proliferation. ATM proliferation and activation can be stimulated by TH2 cytokines, such as IL‐4 and IL‐13, suggesting involvement of CD4‐positive T cells in ATM proliferation and activation. Furthermore, several studies have associated T cells to alterations in glucose metabolism. Therefore, we sought to examine a direct impact of CD4‐positive T cells on ATM activation, ATM proliferation and glucose homeostasis using an in vivo depletion model. Surprisingly, CD4 depletion did not affect ATM activation, ATM proliferation, or insulin sensitivity. However, CD4 depletion led to a significant improvement of glucose tolerance. In line with this, we found moderate disturbances in pancreatic endocrine function following CD4 depletion. Hence, our data suggest that the effect on glucose metabolism observed after CD4 depletion might be mediated by organs other than AT and independent of AT inflammation. Abstract : Obesity induces metabolic imbalance and changes in adipose tissue macrophage (ATM) activation and proliferation. Elaborating on the role of CD4‐positive lymphocytes in obese mice, we found that CD4 depletion led to a partial restoration of obesity‐induced metabolic imbalance, while leaving ATM activation and proliferation unaffected.